The German productivity paradox: Facts and explanations - Steffen Elstner; Lars P. Feld; Christoph M. Schmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Despite massive digitization efforts, the German economy has experienced a marked slowdown in its productivity growth. This paper analyzes the reasons behind this disconcerting development. A major factor is the turnaround of the labor market that commenced around 2005. The successful integration of five million predominantly low-productivity workers into the labor market induced an attenuating effect on productivity growth. This does not explain the slowdown entirely, however. As a potentially important countervailing force, technological advances associated with digitization would have had the potential to lift productivity growth more strongly, but they frequently translated into employment growth instead. – – Trotz erheblicher Anstrengungen bei der Digitalisierung weist die deutsche Volkswirtschaft ein verlangsamtes Wachstum der gesamtwirtschaftlichen Produktivität auf. Dieser Beitrag analysiert die Hintergründe für diese beunruhigende Entwicklung. Eine wichtige Ursache dieses Phänomens sind die massiven Veränderungen am deutschen Arbeitsmarkt, die ihren Anfang in der Mitte des vergangenen Jahrzehnts nahmen. Über fünf Millionen Erwerbstätige wurden seitdem in den Arbeitsmarkt neu integriert, was das Produktivitätswachstum erheblich dämpfte. Der mit der ausgeprägten Digitalisierung der Wirtschaft verbundene gegenläufige Impuls hat diese Verlangsamung nicht völlig kompensiert, da technologische Impulse tendenziell nicht nur in verstärkte Wirtschaftsleistung, sondern auch in Beschäftigungszuwachs übersetzt werden.
Keywords: O40; E24; C32; 330; labor productivity; labor markets; technology shocks; digitalization; structural VARs